2014
DOI: 10.2478/johh-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Parameter estimation of soil hydraulic and thermal property functions for unsaturated porous media using the HYDRUS-2D code

Abstract: Knowledge of soil hydraulic and thermal properties is essential for studies involving the combined effects of soil temperature and water input on water flow and redistribution processes under field conditions. The objective of this study was to estimate the parameters characterizing these properties from a transient water flow and heat transport field experiment. Real-time sensors built by the authors were used to monitor soil temperatures at depths of 40, 80, 120, and 160 cm during a 10-hour long ring infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…On one hand, the numerical inversion of Richards' equation represents a very powerful analytical tool. On the other hand, the numerical inversion of in-situ infiltration experiments was reported to suffer from non-uniqueness due to the lack of information about pressure head, moisture content, or temperature measured (e.g., Nakhaei and Šimůnek, 2014). Probably, for these reasons, a demand for simpler and more robust methods of infiltration experiment data processing persists.…”
Section: Methods For the Evaluation Of Ponded Infiltration Field Expementioning
confidence: 99%
“…On one hand, the numerical inversion of Richards' equation represents a very powerful analytical tool. On the other hand, the numerical inversion of in-situ infiltration experiments was reported to suffer from non-uniqueness due to the lack of information about pressure head, moisture content, or temperature measured (e.g., Nakhaei and Šimůnek, 2014). Probably, for these reasons, a demand for simpler and more robust methods of infiltration experiment data processing persists.…”
Section: Methods For the Evaluation Of Ponded Infiltration Field Expementioning
confidence: 99%
“…Many researchers have reported that cumulative infiltration data do not provide enough information to obtain a unique set of optimized parameters, and some additional information is needed to yield a unique set of optimized parameters in inverse problems (Hopmans et al, 2002;Nakhaei and Šimůnek, 2014;Ritter et al, 2004;Russo et al, 1991). Such additional information could consist of pressure heads and/or water contents (Šimůnek and van Genuchten, 1996), solute concentrations (Abbasi et al, 2003), or temperatures (Nakhaei and Šimůnek, 2014) measured at a certain depth along the soil profile. However, our simulation results show that the simultaneous use of FC and PWP as an input increased the simulation error (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The vadose zone has a fundamental role in many aspects of hydrology, including infiltration, soil moisture storage, evaporation, plant water uptake, groundwater recharge, runoff, and erosion (Nakhaei and Šimůnek, 2014). Knowledge of the hydraulic properties of unsaturated soils (ie the retention curve, θ(h), and the hydraulic conductivity functions, K(h)) is essential for most or all studies involving water flow and solute transport in the vadose zone (Bitterlich et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if a model of soil water movement established under normal isothermal conditions is used to simulate soil water movement under non-isothermal conditions, the results will show a certain degree of deviation. In studying soil water movement, the effect of temperature gradient on soil water movement parameters and of heat flux on soil water movement cannot be ignored [9].…”
Section: Introductionmentioning
confidence: 99%